Determination of superoxide generated by human polymorphonuclear leukocytes by ESR and its clinical application - Morita, Yutaka; Itani, Kenji; Tanigawa, Toru; Yoshida, Norimasa; Miyagawa, Haruo; Takemura, Toshiki; Sugino, Shigeru; Ueda, Shigenobu; Yoshikawa, Toshikazu; Tainaka, Kenzo; Kondo, Motoharu (Ensho, 1988)
Electron spin resonance (ESR) is regarded as the least ambiguous method for the detection of free radicals. Using spin trapping technique with 5, 5-dimethyl-pyrroline-N-oxide (DMPO) we measured superoxide generated by stimulated polymorphonulcear leukocytes (PMN) . The results were compared to those by chemiluminescence study with Cypridina luciferin analog (CLA) which is highly sensetive to superoxide. ESR spectrum was obtained by JEOL-JES-FE2XG ESR spectrometer. The intensity of the signal of DMPO-OOH adduct was measured as ratio to the intensity of Mn2+ signal. Phorbol myristate acetate or opsonized zymosan were used as stimulants of PMN. The ESR signal of DMPO-OOH was completely inhibited by superoxide dismutase, but not affected by catalase or sodium azide. The relative intensity of DMPO-OOH signal and the maximal increase of CLA-dependent chemiluminescence were increased in proportion to the xanthine oxidase unit in hypoxanthine +xanthine oxidase system, and to the cell concentration in PMN system. There were positive correlation between the relative intensity of the ESR signal of DMPO-OOH and CLA-dependent chemiluminescence by stimulatd PMN from patients. By ESR assay, increased generation of superoxide by PMN in patients with fairly controlled diabetes was shown.